2012
DOI: 10.1111/j.1365-4632.2011.05359.x
|View full text |Cite
|
Sign up to set email alerts
|

Economic burden of moderate to severe plaque psoriasis in Canada

Abstract: Projecting the mean costs per patient to the afflicted population yields an estimated total annual cost of $1.7 billion (95% CI: $0.8-$2.6 billion) attributable to moderate to severe psoriasis in Canada. Understanding the interplay between direct costs, lost productivity, and quality of life is critical for accurately identifying and evaluating effective treatments for this disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
45
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 30 publications
5
45
0
Order By: Relevance
“…In the COI analyses conducted by Fonia et al (UK) 353 [28] and Driessen et al (the Netherlands) [29] all patients 354 were treated with biological drugs. The biological treat-355 ment rate was 16 % in the study by Ghatnekar et al 356 (Sweden) [34], 13 % by Levy and colleagues (Canada) 357 [33], 6 % by Steinke et al (Germany) [36] [32]. Only one study by Gleason and 359 colleagues (US) did not report the rate of biological therapy 360 [31].…”
mentioning
confidence: 87%
See 2 more Smart Citations
“…In the COI analyses conducted by Fonia et al (UK) 353 [28] and Driessen et al (the Netherlands) [29] all patients 354 were treated with biological drugs. The biological treat-355 ment rate was 16 % in the study by Ghatnekar et al 356 (Sweden) [34], 13 % by Levy and colleagues (Canada) 357 [33], 6 % by Steinke et al (Germany) [36] [32]. Only one study by Gleason and 359 colleagues (US) did not report the rate of biological therapy 360 [31].…”
mentioning
confidence: 87%
“…361 Studies that provided costs specifically for BST groups 362 or subgroups were selected for comparison. Neither the 363 study by Gleason et al (US) [31] nor the one by Levy et al 364 (Canada) [33] reported costs data for BST group, therefore, 365 these were excluded. Moreover, only eight patients 366 received biological agent in the study by Steinke et al [36] Journal : Large [34] and Le Moigne (France, 2013) [32] 371 (Table 4).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A recent review considered only seven studies dealing with the costs of psoriasis [5]. Psoriasis is is thought to be one of the most costly dermatological diseases due to its high prevalence [6]. Estimates of per-patient costs vary considerably depending on disease severity [7, 8].…”
Section: Introductionmentioning
confidence: 99%
“…Productivity loss due to psoriasis has been estimated to 2-26 days/patient per year, depending on the setting, severity and methods used (6,(24)(25)(26)(27). Treatment with biologics has resulted in decreased absence from work in psoriasis patients (28)(29)(30), but the findings are often limited to clinical trials.…”
mentioning
confidence: 99%